2006
DOI: 10.1099/mic.0.28677-0
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of regulatory cross-talk between P fimbriae and type 1 fimbriae in uropathogenic Escherichia coli

Abstract: The majority of Escherichia coli strains isolated from urinary tract infections have the potential to express multiple fimbriae. Two of the most common fimbrial adhesins are type 1 fimbriae and pyelonephritis-associated pili (Pap). Previous research has shown that induced, plasmid-based expression of a Pap regulator, papB, and its close homologues can prevent inversion of the fim switch controlling the expression of type 1 fimbriae. The aim of the present study was to determine if this cross-regulation occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 56 publications
1
76
0
2
Order By: Relevance
“…In our forced Ag43 expression strains this effect would be enhanced even further as a result of constitutive gene expression (i.e., the genes are already "on"). In support of this model others have demonstrated the existence of an inverse relationship between type 1 fimbrial gene expression and P fimbrial gene expression (20,50,57). It has been proposed that during the course of an infection type 1 fimbriae are important in the early stages; however, as the infection progresses, increased expression of motility and P fimbrial genes occurs at the expense of type 1 fimbrial expression (5).…”
Section: Vol 75 2007mentioning
confidence: 84%
“…In our forced Ag43 expression strains this effect would be enhanced even further as a result of constitutive gene expression (i.e., the genes are already "on"). In support of this model others have demonstrated the existence of an inverse relationship between type 1 fimbrial gene expression and P fimbrial gene expression (20,50,57). It has been proposed that during the course of an infection type 1 fimbriae are important in the early stages; however, as the infection progresses, increased expression of motility and P fimbrial genes occurs at the expense of type 1 fimbrial expression (5).…”
Section: Vol 75 2007mentioning
confidence: 84%
“…The two loci may produce fimbriae that have different specificities or structural properties, or perhaps each locus is required under distinct spatial or temporal conditions and thus responds to different environmental signals. It is known that one pap operon can affect the expression of a second pap or other fimbrial operon present in a strain (24,31). It may be that such cross talk is necessary for function of the two CFT073 pap operons during mouse UTI.…”
Section: Discussionmentioning
confidence: 99%
“…7. This demonstrated that the nadB gene can be used as a neutral site to integrate genes into the chromosome of E. coli, in addition to other possible sites like the lac operon (Holden et al, 2006), the unique insertion site of Tn7 (Craig, 1991) or functionless genes in bacterial genome (Ochman & Davalos, 2006).…”
Section: Application Of Nadb As a Neutral Insertion Site In Upecmentioning
confidence: 99%